Planned Behavior in Supporting Cashless Society in Sharia Financial Institutions - Pradesyah, Riyan; Ismail, Abdul Hadi; Adawiyah, Robiatul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The development of non-cash payments is currently continuing to grow in Indonesia, many applications continue to develop their applications towards a cashless society, but many people and MSMEs are still reluctant to use the non-cash payment system, due to several factors that they consider to be very detrimental to users or providers. non-cash payments. This research aims to examine attitude variables, subjective norms, and behavioral control on the behavior of halal MSMEs in using non-cash payments through interest variables. The approach used in the research is a quantitative approach, with the SmartPLS analysis tool. The results obtained show that the attitude variable (X1) influences the behavior of MSMEs in using non-cash payments (Y) through the interest variable (Z). The subjective norm variable (X2) does not affect MSME behavior in using non-cash payments (Y) through the interest variable (Z). The behavioral control variable (X3) influences the behavior of MSMEs in using non-cash payments (Y) through the interest variable (Z).